Tipos de muestra en la relación diámetro – altura comercial en las plantas de Iryanthera tricornis Ducke “pucuna caspi” en bosque natural. Puerto Almendra, Loreto, Perú – 2023 - Romayna Dávila, Josemaría (2024)
The objective of the study was to determine the ideal sample type for the diameter-commercial height relationship in Iryanthera tricornis Ducke "pucuna caspi" trees in natural forest, Puerto Almendra, Loreto, Peru - 2023. Three samples were evaluated, two with diameter classes and one without. Results showed that sample 2, with 9 diameter classes and 2-centimeter, with common variations among them of 92%. The prediction equations for the diameter commercial height relationship are as follows: Y= 3.315 x (1.050 t) Compound; Y= e (1.198 (0.049 x t)) Growth; Y= 3.315 (e (0.049 x t)) Exponential; Y= 1/(1/u + 0.302 (0.952t)) Logistic.